Lexical heterogeneity in Relaciones Geográficas of the Government of Yucatán (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
Relaciones Geográficas are texts in Spanish that aim at obtaining reliable descriptions from the colonialism period. Previous research with very different repertoires have established that lexical heterogeneity is a common trend in the entire colonial written production. The objective of this research is to check whether a particular repertoire, such as relations of the Government of Yucatán (1579-1581) represents a homogeneous or heterogeneous body of indigenous loans incorporation.Quantitative and qualitative methodologies are used to analyse the potential lexical plurality of these texts which are associated with certain specific factors. The findings corroborate that lexical heterogeneity is present, despite being a uniform corpus, and show three different trends when including prehispanic concepts in Spanish documents.
Keywords: Lexical indigenisms; Relaciones Geográficas; Yucatán